Functional material for concrete capable of resisting erosion of high-concentration composite salt

By using functional materials in concrete, combined with granulated blast furnace slag powder, modified red mud and magnesium oxide, the problem of concrete erosion in ultra-high concentration composite salt environment is solved, and the corrosion resistance and structural stability are significantly improved.

CN119874245AActive Publication Date: 2025-04-25XINJIANG WATER RESOURCES & HYDROPOWER SURVEY DESIGN & RES INST CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510050563.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

In an environment of ultra-high concentration composite salt, concrete faces the dual challenges of physical and chemical erosion, resulting in reduced strength, threatened structural stability, and shortened service life.

Method used

A functional material is used, including functional fillers, water reducers, sulfate corrosion resistance, anti-chlorine corrosion agent, preservatives and gas induction agents. By combining the use of granulated blast furnace slag powder and molybdenum tailings powder, modified red mud and modified magnesium-aluminum hydrotalcite, magnesium oxide and drift beads, the corrosion resistance of concrete is improved.

Benefits of technology

It significantly improves the sulfate and chloride corrosion resistance of concrete, enhances its mechanical properties and structural stability, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239836450000102
    Figure BDA0005239836450000102
  • Figure BDA0005239836450000111
    Figure BDA0005239836450000111
  • Figure BDA0005239836450000113
    Figure BDA0005239836450000113
Patent Text Reader

Abstract

The invention discloses a concrete functional material capable of resisting high-concentration composite salt erosion. Comprising the following components in parts by weight: 150-300 parts of functional filler, 10-20 parts of a water reducing agent, 15-30 parts of a sulfate corrosion resistant agent, 20-40 parts of a chlorine salt corrosion resistant agent, 2-5 parts of a preservative and 5-10 parts of an air entraining agent. The functional material is used for preparing concrete, and the strength, sulfate corrosion resistance and chlorine salt corrosion resistance of the concrete are improved. The granulated blast-furnace slag powder and the molybdenum tailing powder in the material components are combined for use, so that the mechanical property of the concrete is improved; the modified red mud and the modified magnesium-aluminum hydrotalcite are combined for use, so that the sulfate corrosion resistance of the concrete is improved; the magnesium oxide and the floating beads are combined for use, so that the chlorine salt erosion resistance of the concrete is improved, and synergistic interaction is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to a functional material for concrete which can resist corrosion by high-concentration composite salt. Background Art

[0002] In an environment with ultra-high concentration of composite salt, concrete will face the dual challenges of physical and chemical erosion. From a physical perspective, ultra-high concentration of sulfate in the pores of concrete will continue to dissolve and crystallize as the temperature and humidity of the environment change. The volume of the formed crystals will expand, generating huge crystallization pressure, which will damage the internal pore structure of the concrete, cause cracks to form and expand, and lead to reduced strength of concrete, surface erosion, and even structural disintegration in severe cases. From a chemical perspective, sulfate reacts with cement hydration products in concrete to form expansive substances such as calcium sulfonate and gypsum. The large amount of calcium sulfonate generated will significantly increase the solid phase volume of concrete, generate internal stress, cause concrete expansion and cracking, and make the internal structure loose, accelerating the deterioration of concrete and destroying the internal structure of concrete. Ultra-high concentration of chloride salt will destroy the passivation film of steel bars in concrete, expose steel bars to corrosive environment, cause steel bar corrosion, cause steel bar volume expansion, and then cause the concrete protective layer to crack and peel off, seriously weakening the bearing capacity of the structure. Under the coupled erosion of multiple factors such as high-concentration sulfate and chloride salts, the degree of erosion of concrete is aggravated due to the interaction of factors such as temperature, humidity and concrete stress changes in the environment. The salt solubility increases at high temperatures, and crystallization is more likely to occur after cooling. High humidity promotes salt dissolution and diffusion, and dry-wet cycles accelerate surface salting out and crystallization, greatly accelerating the erosion rate. When concrete is eroded by composite salts and its performance deteriorates, its bearing capacity will inevitably decrease, and its structural stability will be seriously threatened, which will greatly shorten the service life of the water conservancy project.

[0003] Large-scale, ultra-high concentration composite salt erosion environments are rarely seen in previous projects, and there are no ready-made engineering application cases to learn from in terms of concrete prevention and control technology. If the technical measures taken are inappropriate, it will bring hidden dangers of erosion and damage to the concrete, resulting in a significant reduction in the expected life of the project. Therefore, conducting research on the damage of ultra-high concentration composite salts to concrete can not only resist multiple erosion threats and ensure that concrete has good durability, but also ensure that concrete maintains good mechanical properties for a long time in a composite salt environment, so that it can stably withstand various external loads and improve the stability of the engineering structure. Summary of the invention

[0004] The object of the present invention is to provide a functional material for concrete which can resist corrosion by high-concentration composite salt.

[0005] A functional material for concrete capable of resisting high-concentration composite salt erosion comprises the following components in parts by weight: 150-300 parts of functional filler, 10-20 parts of water reducing agent, 15-30 parts of anti-sulfate erosion agent, 20-40 parts of anti-chloride salt erosion agent, 2-5 parts of preservative and 5-10 parts of air entraining agent.

[0006] The functional filler is one or more of limonite powder, wollastonite powder, sepiolite powder, granulated blast furnace slag powder, molybdenum tailings powder, iron tailings powder, and bentonite tailings powder.

[0007] The functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1.

[0008] The water reducer is one or more of calcium lignin sulfonate, sodium lignin sulfonate, propanesulfonic acid lignin ether, TH-928 water reducer, and ASP aminosulfonate high-efficiency water reducer.

[0009] The anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium aluminum hydrotalcite in a mass ratio of 2:1.

[0010] The modified red mud is prepared by the following method: taking red mud and crushing it to 300-600 meshes, adding 0.5-2 times the weight of water, adjusting the pH to 8-9, adding 3-aminopropyltriethoxysilane accounting for 10-20% of the mass of the red mud, stirring the reaction for 1-3 hours, roasting at 150-250° C. for 1-3 hours, and cooling to room temperature to obtain the modified red mud.

[0011] The modified magnesium aluminum hydrotalcite is prepared by the following method: calcining the magnesium aluminum hydrotalcite at a temperature of 500-700°C for 30-60 minutes to obtain the calcined magnesium aluminum hydrotalcite, and crushing the calcined magnesium aluminum hydrotalcite to 300-600 meshes; taking the calcined magnesium aluminum hydrotalcite, adding 2-4 times the mass of anhydrous ethanol, and then adding titanate accounting for 3-8% of the mass of the magnesium aluminum hydrotalcite, stirring at a constant temperature of 60-85°C for 80-120 minutes, stopping stirring and keeping warm for 1-3 hours until the anhydrous ethanol is completely volatilized, and cooling to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0012] The anti-chloride salt corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0013] The preservative is one or more of sodium methylparaben, sodium ethylparaben, boric acid, p-hydroxybenzoate, and sodium diacetate; the air entraining agent is one or more of rosin soap, sodium dodecylbenzene sulfonate, sodium fatty alcohol polyoxyethylene ether sulfonate, and ZY-99.

[0014] The functional material for concrete capable of resisting corrosion by high-concentration composite salt is used in the preparation of concrete.

[0015] Beneficial effects of the present invention: The functional material of the present invention is used to prepare concrete, and improves the strength and resistance to sulfate and chloride corrosion of concrete. Granulated blast furnace slag powder and molybdenum tailings powder are used in combination in the material components to improve the mechanical properties of concrete; modified red mud and modified magnesium aluminum hydrotalcite are used in combination to improve the resistance to sulfate corrosion of concrete; magnesium oxide and floating beads are used in combination to improve the resistance to chloride corrosion of concrete, and synergistically enhance the effect. DETAILED DESCRIPTION

[0016] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0017] Example 1

[0018] A functional material for concrete capable of resisting corrosion from high-concentration composite salts comprises the following components in parts by weight: 200 parts of functional filler, 15 parts of calcium lignin sulfonate, 20 parts of an anti-sulfate corrosion agent, 30 parts of an anti-chloride corrosion agent, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium aluminum hydrotalcite in a mass ratio of 2:1; and the anti-chloride corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0019] The modified red mud is prepared by the following method: taking red mud and crushing it to 500 mesh, adding 1 weight portion of water, adjusting the pH to 8.5, adding 3-aminopropyltriethoxysilane accounting for 15% of the mass of the red mud, stirring the reaction for 2 hours, roasting at 200° C. for 2 hours, and cooling to room temperature to obtain modified red mud.

[0020] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 600°C for 45 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 500 meshes; the calcined magnesium aluminum hydrotalcite is taken, 3 times the mass of anhydrous ethanol is added, and then titanate accounting for 6% of the mass of the magnesium aluminum hydrotalcite is added, and the mixture is stirred at a constant temperature of 75°C for 100 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0021] Example 2

[0022] A functional material for concrete capable of resisting corrosion by high-concentration composite salts comprises the following components in parts by weight: 80 parts of limonite powder, 80 parts of wollastonite powder, 12 parts of sodium lignin sulfonate, 16 parts of an anti-sulfate corrosion agent, 22 parts of an anti-chloride corrosion agent, 2 parts of sodium ethylparaben, and 5 parts of rosin soap; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium-aluminum hydrotalcite in a mass ratio of 2:1; the anti-chloride corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0023] The modified red mud is prepared by the following method: taking red mud and crushing it into 350 meshes, adding 0.5 times the weight of water, adjusting the pH to 8, adding 3-aminopropyltriethoxysilane accounting for 10% of the mass of the red mud, stirring the reaction for 3 hours, roasting at 150° C. for 3 hours, and cooling to room temperature to obtain modified red mud.

[0024] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 500°C for 30 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 300 meshes; the calcined magnesium aluminum hydrotalcite is taken, 2 times the mass of anhydrous ethanol is added, and then 3% of the mass of titanate is added to the magnesium aluminum hydrotalcite, and the mixture is stirred at a constant temperature of 60°C for 80 minutes, and the stirring is stopped and the mixture is kept warm for 3 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0025] Example 3

[0026] A functional material for concrete capable of resisting corrosion from high-concentration composite salts comprises the following components in parts by weight: 150 parts of iron tailings powder, 150 parts of bentonite tailings powder, 20 parts of TH-928 water reducer, 30 parts of anti-sulfate corrosion agent, 40 parts of anti-chloride corrosion agent, 5 parts of p-hydroxybenzoic acid ester, and 10 parts of sodium fatty alcohol polyoxyethylene ether sulfonate; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium aluminum hydrotalcite in a mass ratio of 2:1; the anti-chloride corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0027] The modified red mud is prepared by the following method: taking red mud and crushing it to 600 mesh, adding 2 times the weight of water, adjusting the pH to 9, adding 3-aminopropyltriethoxysilane accounting for 20% of the mass of the red mud, stirring the reaction for 3 hours, roasting at 250° C. for 1 hour, and cooling to room temperature to obtain modified red mud.

[0028] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 700°C for 30 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 600 meshes; the calcined magnesium aluminum hydrotalcite is taken, 4 times the mass of anhydrous ethanol is added, and then 8% of the mass of titanate is added, and the mixture is stirred at a constant temperature of 85°C for 120 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0029] Comparative Example 1

[0030] A functional material for concrete capable of resisting corrosion by high-concentration composite salts comprises the following components in parts by weight: 200 parts of granulated blast furnace slag powder, 15 parts of calcium lignin sulfonate, 20 parts of an anti-sulfate corrosion agent, 30 parts of an anti-chloride corrosion agent, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium aluminum hydrotalcite in a mass ratio of 2:1; the anti-chloride corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0031] The modified red mud is prepared by the following method: taking red mud and crushing it to 500 mesh, adding 1 weight portion of water, adjusting the pH to 8.5, adding 3-aminopropyltriethoxysilane accounting for 15% of the mass of the red mud, stirring the reaction for 2 hours, roasting at 200° C. for 2 hours, and cooling to room temperature to obtain modified red mud.

[0032] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 600°C for 45 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 500 meshes; the calcined magnesium aluminum hydrotalcite is taken, 3 times the mass of anhydrous ethanol is added, and then titanate accounting for 6% of the mass of the magnesium aluminum hydrotalcite is added, and the mixture is stirred at a constant temperature of 75°C for 100 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0033] Comparative Example 2

[0034] A functional material for concrete capable of resisting corrosion from high-concentration composite salts comprises the following components in parts by weight: 200 parts of molybdenum tailings powder, 15 parts of calcium lignin sulfonate, 20 parts of an anti-sulfate corrosion agent, 30 parts of an anti-chloride corrosion agent, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium aluminum hydrotalcite in a mass ratio of 2:1; the anti-chloride corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0035] The modified red mud is prepared by the following method: taking red mud and crushing it to 500 mesh, adding 1 weight portion of water, adjusting the pH to 8.5, adding 3-aminopropyltriethoxysilane accounting for 15% of the mass of the red mud, stirring the reaction for 2 hours, roasting at 200° C. for 2 hours, and cooling to room temperature to obtain modified red mud.

[0036] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 600°C for 45 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 500 meshes; the calcined magnesium aluminum hydrotalcite is taken, 3 times the mass of anhydrous ethanol is added, and then titanate accounting for 6% of the mass of the magnesium aluminum hydrotalcite is added, and the mixture is stirred at a constant temperature of 75°C for 100 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0037] Comparative Example 3

[0038] A functional material for concrete capable of resisting corrosion by high-concentration composite salts comprises the following components in parts by weight: 200 parts of functional filler, 15 parts of calcium lignin sulfonate, 20 parts of modified red mud, 30 parts of chloride corrosion resistance agent, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1; the chloride corrosion resistance agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0039] The modified red mud is prepared by the following method: taking red mud and crushing it to 500 mesh, adding 1 weight portion of water, adjusting the pH to 8.5, adding 3-aminopropyltriethoxysilane accounting for 15% of the mass of the red mud, stirring the reaction for 2 hours, roasting at 200° C. for 2 hours, and cooling to room temperature to obtain modified red mud.

[0040] Comparative Example 4

[0041] A functional material for concrete capable of resisting corrosion by high-concentration composite salts comprises the following components in parts by weight: 200 parts of functional filler, 15 parts of calcium lignin sulfonate, 20 parts of modified magnesium aluminum hydrotalcite, 30 parts of chloride corrosion resistance agent, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1; the chloride corrosion resistance agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0042] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 600°C for 45 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 500 meshes; the calcined magnesium aluminum hydrotalcite is taken, 3 times the mass of anhydrous ethanol is added, and then titanate accounting for 6% of the mass of the magnesium aluminum hydrotalcite is added, and the mixture is stirred at a constant temperature of 75°C for 100 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0043] Comparative Example 5

[0044] A functional material for concrete capable of resisting corrosion by high-concentration composite salts comprises the following components in parts by weight: 200 parts of functional filler, 15 parts of calcium lignin sulfonate, 20 parts of an anti-sulfate corrosion agent, 30 parts of an anti-chloride corrosion agent, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1; the anti-sulfate corrosion agent is a mixture of red mud and magnesium aluminum hydrotalcite in a mass ratio of 2:1; and the anti-chloride corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:1.

[0045] Comparative Example 6

[0046] A functional material for concrete capable of resisting corrosion by high-concentration composite salts comprises the following components in parts by weight: 200 parts of a functional filler, 15 parts of calcium lignin sulfonate, 20 parts of an anti-sulfate corrosion agent, 30 parts of magnesium oxide, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium-aluminum hydrotalcite in a mass ratio of 2:1.

[0047] The modified red mud is prepared by the following method: taking red mud and crushing it to 500 mesh, adding 1 weight portion of water, adjusting the pH to 8.5, adding 3-aminopropyltriethoxysilane accounting for 15% of the mass of the red mud, stirring the reaction for 2 hours, roasting at 200° C. for 2 hours, and cooling to room temperature to obtain modified red mud.

[0048] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 600°C for 45 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 500 meshes; the calcined magnesium aluminum hydrotalcite is taken, 3 times the mass of anhydrous ethanol is added, and then titanate accounting for 6% of the mass of the magnesium aluminum hydrotalcite is added, and the mixture is stirred at a constant temperature of 75°C for 100 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0049] Comparative Example 7

[0050] A functional material for concrete capable of resisting corrosion from high-concentration composite salts comprises the following components in parts by weight: 200 parts of a functional filler, 15 parts of calcium lignin sulfonate, 20 parts of an anti-sulfate corrosion agent, 30 parts of floating beads, 3 parts of sodium methyl paraben, and 8 parts of sodium dodecylbenzene sulfonate; the functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:1; the anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium-aluminum hydrotalcite in a mass ratio of 2:1.

[0051] The modified red mud is prepared by the following method: taking red mud and crushing it to 500 mesh, adding 1 weight portion of water, adjusting the pH to 8.5, adding 3-aminopropyltriethoxysilane accounting for 15% of the mass of the red mud, stirring the reaction for 2 hours, roasting at 200° C. for 2 hours, and cooling to room temperature to obtain modified red mud.

[0052] The modified magnesium aluminum hydrotalcite is prepared by the following method: the magnesium aluminum hydrotalcite is calcined at 600°C for 45 minutes to obtain the calcined magnesium aluminum hydrotalcite, and the calcined magnesium aluminum hydrotalcite is crushed to 500 meshes; the calcined magnesium aluminum hydrotalcite is taken, 3 times the mass of anhydrous ethanol is added, and then titanate accounting for 6% of the mass of the magnesium aluminum hydrotalcite is added, and the mixture is stirred at a constant temperature of 75°C for 100 minutes, and the stirring is stopped and kept warm for 2 hours until the anhydrous ethanol is completely volatilized, and the mixture is cooled to room temperature to obtain the modified magnesium aluminum hydrotalcite.

[0053] Experimental example:

[0054] Preparation of concrete specimens: according to a water-binder ratio of 0.32, take ordinary Portland cement and water, add 20% fly ash and 8% functional materials (prepared in Examples 1-3 and Comparative Examples 1-7, respectively) accounting for the mass of ordinary Portland cement, stir evenly, put into a mold for forming, and then cure for 28 days at an ambient temperature of 20±2°C and a humidity greater than 95%.

[0055] The compressive strength of concrete prepared by using the functional materials of Examples 1-3 and Comparative Examples 1-2 was measured. Each group of experiments was measured 3 times and the average value was taken. The experimental results were statistically analyzed using SPSS24.0 software. The quantitative data results were used to (mean ± standard deviation) was expressed, and the Kolmogorov-Smirnov test was used for data normality test. For data that met the normal distribution, the mean difference between the two groups was compared using the t test, and the difference was considered statistically significant when P < 0.05. The performance test results are shown in Table 1:

[0056] Table 1

[0057] Experimental Group Compressive strength MPa Example 1 58.8±1.1 Example 2 59.1±1.2 Example 3 57.3±2.5 Comparative Example 1 49.9±1.2* Comparative Example 2 48.8±2.1*

[0058] Note: * represents p<0.05 compared with Example 1.

[0059] The concrete performance test (concrete prepared with the functional materials of Examples 1-3 and Comparative Examples 3-5) was carried out with reference to the Standard for Test Methods for Long-term Performance and Durability of Concrete (GB / T 50082-2024). The dry-wet cycle was repeated 150 times. Each group of experiments was measured 3 times and the average value was taken. The experimental results were statistically analyzed using SPSS24.0 software. The quantitative data results were analyzed using The Kolmogorov-Smirnov test method was used to test the normality of the data. For data that conformed to the normal distribution, the t-test was used to compare the mean differences between the two groups. The difference was considered statistically significant when P < 0.05. The performance test results are shown in Table 2:

[0060] Table 2

[0061]

[0062]

[0063] Note: * represents p<0.05 compared with Example 1.

[0064] According to the RCM method of the chloride ion penetration test in GB / T 50082-2024, the electromigration experiment and the chloride ion penetration depth test were carried out according to the standard, and the non-steady-state chloride ion migration coefficient of the concrete (concrete prepared by the functional materials of Examples 1-3 and Comparative Examples 6-7) and the total electric flux through the concrete specimens for 6 hours were calculated. Each group of experiments was measured 3 times and the average value was taken. The experimental results were statistically analyzed using SPSS24.0 software, and the quantitative data results were used to calculate the total electric flux of the concrete specimens for 6 hours. The Kolmogorov-Smirnov test method was used for data normality test. For data that conformed to normal distribution, the t-test was used to compare the mean differences between the two groups. The difference was considered statistically significant when P < 0.05. The performance test results are shown in Table 3:

[0065] Table 3

[0066]

[0067] Note: * represents p<0.05 compared with Example 1.

[0068] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A functional material for concrete that can resist corrosion from high-concentration composite salts, characterized in that: The invention comprises the following components in parts by weight: 150-300 parts of functional filler, 10-20 parts of water reducing agent, 15-30 parts of anti-sulfate corrosion agent, 20-40 parts of anti-chloride corrosion agent, 2-5 parts of preservative and 5-10 parts of air entraining agent.

2. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 1, characterized in that: The functional filler is one or more of limonite powder, wollastonite powder, sepiolite powder, granulated blast furnace slag powder, molybdenum tailings powder, iron tailings powder, and bentonite tailings powder.

3. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 2, characterized in that: The functional filler is a mixture of granulated blast furnace slag powder and molybdenum tailings powder in a mass ratio of 1:

1.

4. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 1, characterized in that: The water reducer is one or more of calcium lignin sulfonate, sodium lignin sulfonate, propanesulfonic acid lignin ether, TH-928 water reducer, and ASP aminosulfonate high-efficiency water reducer.

5. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 1, characterized in that: The anti-sulfate corrosion agent is a mixture of modified red mud and modified magnesium aluminum hydrotalcite in a mass ratio of 2:

1.

6. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 5, characterized in that: The modified red mud is prepared by the following method: taking red mud and crushing it to 300-600 meshes, adding 0.5-2 times the weight of water, adjusting the pH to 8-9, adding 3-aminopropyltriethoxysilane accounting for 10-20% of the mass of the red mud, stirring the reaction for 1-3 hours, roasting at 150-250° C. for 1-3 hours, and cooling to room temperature to obtain the modified red mud.

7. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 5, characterized in that: The modified magnesium aluminum hydrotalcite is prepared by the following method: calcining the magnesium aluminum hydrotalcite at a temperature of 500-700°C for 30-60 minutes to obtain the calcined magnesium aluminum hydrotalcite, and crushing the calcined magnesium aluminum hydrotalcite to 300-600 meshes; taking the calcined magnesium aluminum hydrotalcite, adding 2-4 times the mass of anhydrous ethanol, and then adding titanate accounting for 3-8% of the mass of the magnesium aluminum hydrotalcite, stirring at a constant temperature of 60-85°C for 80-120 minutes, stopping stirring and keeping warm for 1-3 hours until the anhydrous ethanol is completely volatilized, and cooling to room temperature to obtain the modified magnesium aluminum hydrotalcite.

8. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 1, characterized in that: The anti-chloride salt corrosion agent is a mixture of magnesium oxide and floating beads in a mass ratio of 1:

1.

9. The functional material for concrete capable of resisting corrosion by high-concentration composite salt according to claim 1, characterized in that: The preservative is one or more of sodium methylparaben, sodium ethylparaben, boric acid, p-hydroxybenzoate, and sodium diacetate; the air entraining agent is one or more of rosin soap, sodium dodecylbenzene sulfonate, sodium fatty alcohol polyoxyethylene ether sulfonate, and ZY-99.

10. Use of the functional material for concrete capable of resisting corrosion by high-concentration composite salts according to claim 1 in preparing concrete.

Citation Information

Patent Citations

  • Chlorine ion adsorption material for improving chlorine ion erosion resistance of concrete

    CN110128051A

  • High-corrosion-resistance low-shrinkage concrete and preparation method thereof

    CN114105564A

  • Concrete with chlorine salt erosion resistance function and preparation method thereof

    CN115838260A

  • Corrosion resistant mortar composition

    JP2017132667A

  • Functional mortar composition for repairing-reinforcing concrete structure and repairing-reinforcing method of concrete structure

    KR101936062B1